Building Integrated Solar Thermal Design: Assessment of Performances of a Low Cost Solar Wall in a Typical Italian Building. (June 2016) - Beccali, Marco; Leone, Giuliana; Caputo, Paola; Ferrari, Simone
Abstract: Present work deals with the topic of building integration of solar thermal collector (BIST) as a refurbishment measure. Such equipment, more than its main function as heating generator, plays a specific role as a building component (envelope finishes, thermal insulation layer, roof cover etc). Consequently, from a heat transfer point of view, an integrated component affects twice the global building balance: supporting the thermal plant (i.e. providing heat for final uses) and modifying the wall heat-transfer pattern (i.e. reducing thermal losses). In turn, the collector performance itself is influenced by the wall structure (back losses reduction). Present work proposes a method for evaluating the yearly performance of a low cost BIST by means of a Trnsys model on a reference building. This model arises from previous studies based on experimental validation of a FEM model that was implemented in order to describe the collector-wall system efficiency.